Introduction to plasmas and plasma dynamics : with reviews of applications in space propulsion, magnetic fusion, space physics - York, Thomas M.; Tang, Haibin (Engineering professional collection, 2015)
Introduction to Plasmas and Plasma Dynamics provides an accessible introduction to the understanding of high temperature, ionized gases necessary to conduct research and develop applications related to plasmas. While standard presentations of introductory material emphasize physics and the theoretical basis of the topics, this text acquaints the reader with the context of the basic information and presents the fundamental knowledge required for advanced work or study. The book relates theory to relevant devices and mechanisms, presenting a clear outline of analysis and mathematical detail; it highlights the significance of the concepts with reviews of recent applications and trends in plasma engineering, including topics of plasma formation and magnetic fusion, plasma thrusters and space propulsion.